REKOMENDASI PEMBERIAN BEASISWA KARTU JAKARTA PINTAR DI SMAN 76 JAKARTA MENGGUNAKAN ALGORITMA FUZZY - Mochamad Sofyan Muttaqin (2020)
Jakarta Pintar Card is one of the DKI Jakarta provincial government programs to assist in the Cost of Quality Improvement of Education for elementary to high school students from economically disadvantaged families. Currently, the Jakarta Smart Card scholarship selection is still using a conventional system that causes inaccuracies in the selection of prospective scholarship recipients. Therefore, in this study, a decision support system was designed to recommend students to determine the Jakarta Smart Card scholarship recipients using the fuzzy algorithm. With these problems, of course, we need a system that can reduce the problems that occur. The fuzzy method is a lot of logic that can define values between conventional conditions such as true or false. In fuzzy logic, a way to understand system performance by assessing inputs as calculations and outputs as a result of calculations. The results of this study are in the form of a decision support system for the determination of scholarship qualifications based on the desired criteria, and this system produces data accuracy values with manual calculations resulting in a difference of 0.11606 % or a success rate of 98%.